PENGARUH PEMBERIAN GEL ALOE VERA TERHADAP SKALA PLEBITIS PADA PASIEN RAWAT INAP DI RSU DR. WAHIDIN SUDIROHUSODO KOTA MOJOKERTO - Binarti Dwi W (Jurnal Keperawatan, 2016)
Plebitis if left untreated, can cause the thrombus and emboli that may cause permanent damage to the vein and can cause infection. The goal of research to know how the granting of the gel of Aloe vera against the scale plebitis. Design research is indicated with pre type architecture one group pre and post test design. The granting of study variable gel aloe vera as the independent variable and the dependent variable as a phlebitis scale. The population of the study i.e. the whole plebitis sufferers in the Wahidin Sudiro Husodo Hospital in Mojokerto on 05-06 September 2015. Samples taken with the technique of sampling as much as concecutive 19 respondents. The data collected with phlebitis scale observation sheet and tested with the Wilcoxon test. The results showed there is a change on the scale of phlebitis experienced by respondents are experiencing change, from respondents who were previously not found that there were no symptoms of phlebitis after granting gel aloevera 7 respondents that there are no symptoms, the Wilcoxon test results indicate data that ρ = 0.001<α = 0.05 so that ρ H0 is rejected and H1 are received so that the influence of the giving of the Aloe vera gel against phlebitis scale. Any change that occurs in patients who have experienced phlebitis pointed out that granting therapy gel aloe vera can indicate the results of the changes that are quite effective. Expected health care personnel can apply nonfarmakologis therapy such as aloe vera gel so that the services provided can be more berkualtias as well as the handling is done with more precise.